2023
DOI: 10.7717/peerj.16116
|View full text |Cite
|
Sign up to set email alerts
|

Numbers of fish species, higher taxa, and phylogenetic similarity decrease with latitude and depth, and deep-sea assemblages are unique

Han-Yang Lin,
Shane Wright,
Mark John Costello

Abstract: Species richness has been found to increase from the poles to the tropics but with a small dip near the equator over all marine fishes. Phylogenetic diversity measures offer an alternative perspective on biodiversity linked to evolutionary history. If phylogenetic diversity is standardized for species richness, then it may indicate places with relatively high genetic diversity. Latitudes and depths with both high species and phylogenetic diversity would be a priority for conservation. We compared latitudinal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…These findings are supported by other scholars, such as Lin et al [38], who studied marine fish at various taxonomic levels and observed decreased species diversity at the equator, with the Northern Hemisphere having greater species diversity. In another study, Lin et al [39] found that the number of fish species with higher taxon and phylogenetic similarity decreases with latitude and ocean depth because of climate change. Lin and Costello [40] also found that fish body size and trophic level increase with latitude because of climate change, likely because of changes in temperature and oxygen levels.…”
Section: Impact Of Climate Change On Marine Biodiversitymentioning
confidence: 97%
“…These findings are supported by other scholars, such as Lin et al [38], who studied marine fish at various taxonomic levels and observed decreased species diversity at the equator, with the Northern Hemisphere having greater species diversity. In another study, Lin et al [39] found that the number of fish species with higher taxon and phylogenetic similarity decreases with latitude and ocean depth because of climate change. Lin and Costello [40] also found that fish body size and trophic level increase with latitude because of climate change, likely because of changes in temperature and oxygen levels.…”
Section: Impact Of Climate Change On Marine Biodiversitymentioning
confidence: 97%